Expanding contraceptive options in South Africa : knowledge, attitudes, and practices surrounding the intrauterine device (IUD) - Gutin, Sarah Anne (Women's Health Research Unit, 2017)
The intrauterine device (IUD) is a safe, effective, convenient, reliable, inexpensive, and cost-effective form of reversible contraception. It rivals female sterilization, injectables, and implants with respect to effectiveness in pregnancy prevention. Once inserted, IUDs are nearly maintenance free; some IUDs can even be used for over a decade. In many settings however, the utilization of this form of contraception is poor and a number of barriers to usage exist. These barriers often relate to lack of knowledge and misperceptions among both potential users and healthcare providers. The IUD is a reliable option that may be an ideal form of contraception for many women in South Africa. In order to make this method available on a wider scale, it is necessary to provide correct information to women and health care professionals and to increase the availability and use of this highly effective method. We conducted a cross-sectional descriptive study designed to assess the current knowledge, attitudes, and practices of potential users and health care providers with respect to the IUD. We recruited 205 women between 15 to 49 years of age who were attending family planning and ST! care services at four primary level public clinics (two in the more urban Western Cape Province and two in the rural Eastern Cape Province in South Africa). In addition, we interviewed 32 providers from 12 clinics (six clinics per province). Ethical approval for this research was obtained from both the University of Cape Town and Walter Sisulu University (formerly the University of the Transkei). Permission was also given by the local and provincial health services. Among clients, knowledge of the IUD was poor. About 26% of women had heard of the IUD. After the method was explained to them, 89.7% of women believed that there were advantages to using the IUD and 72.7% of women said that they would consider using the JUD in the future. Also, women thought the IUD was an easier contraceptive method to use than oral contraceptive pills, injectables, male and female condoms, and female sterilization. Logistic regression modelling showed that, after adjusting for level of education, being from the Western Cape, older age, and having heard of emergency contraception all independently predicted awareness of the IUD method. For the most part, providers knew how the IUD worked to prevent pregnancy; however, providers were lacking in more detailed knowledge about the method and had misinformation about the IUD. Almost all (93 .6%) of providers recognized their need for more information and training about the IUD. Providers reported that barriers to IUD usage in South Africa were lack of knowledge of the method on the part of providers (84.4%), a lack of trained providers to insert or remove the IUD (62.5%), limited availability of the device at health facilities (56.3%), and a lack of knowledge on the part of potential users (46.9%). Despite these barriers, 81 % of providers believed women would be interested in the IUD if they knew about it and 73.3% believed the IUD should be promoted in South Africa. Our results suggest that the IUD would be a welcome addition to the contraceptive method mix in South Africa and that both clients and providers would be interested in this method. It is clear that awareness campaigns among women seeking contraception would be necessary for building support and publicizing the IUD. It will also be necessary to train and educate providers, focusing on up to date information, dispelling myths, and proper insertion and removal techniques. South Africa could re-introduce the IUD into the contraceptive method mix and increase women's choice by adding this valuable, viable, and sustainable option to the contraceptive method mix. The findings of this study, which was requested by the provincial health services, will be used to inform policy and as a starting point for assessing the feasibility and acceptability of a greater role for the IUD in the contraceptive method mix in South Africa.